Green synthesis and antibacterial activity of Cadmium Sulﬁde Nanoparticles using Panicum sarmentosum - Yong, Shi Yi (2018)
This study presents a green approach on synthesizing cadmium sulﬁde nanoparticles using plant Panicum sarmentosum. The prepared cadmium sulﬁde nanoparticles were characterized by UV- Visible spectrophotometer, X- Ray Diffraction (XRD), Fourier Transformation Infrared (FTIR), Scanning Electron Microscope (SEM), X- Ray Fluorescence (XRF) and Thennal Gravimetric Analysis (TGA) respectively. The UV- Vis spectroscopy analysis revealed the formation of cadmium sulﬁde nanoparticles by exhibiting the typical surface Plasmon absorption maxima at a wavelength between 300- 400 nm as observed. XRD analysis result revealed the cubic shape with size 4.6 nm of CdSNPs. SEM obtained the infonnation regarding to the surface morphology. XRF analysis conﬁrmed the presence of cadmium and sulphur in nanoparticles. TGA result proven that CdSNPs is more thermal stable than plant material. The presence of alcohol/phenol (OH), amide (NH) and carboxylic functional group were conﬁrmed by FTIR analysis. Antibacterial activity of CdSNPs against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) was accomplished by agar Well diffusion method with increasing concentration of nanoparticles and enlarged inhibition zone was noticed. The characterization results revealed that cadmium sulﬁde nanoparticles were successfully synthesized through Panicum sarmentosum as well as the outcome of antibacterial activity showed that the synthesized cadmium sulﬁde nanoparticles had an inhibiting activity against Escherichia coli and Staphylococcus aureus.